Mandibular reconstruction with fibula flap microsurgical of the Institute of Child Health Specialist, Lima, Peru - Oré Acevedo, Juan Francisco (2009)
Introducction: mandible reconstruction, an important area within heat and neck surgery, is atopic with constant innovation with plenty of debate and scientific contributions that allow physicians to have adequate therapy for extensive tumors that may leave aesthetic and functional sequels.Clinical cases. The cases that underwent a large surgical resection and required a microsurgical fibula free flap for a mandible tumor were reviewed between January 2004 to August 2008; by the Head, Neck and Maxillofacial Surgery department at the National Pediatric Health Institute. Four cases were taken part in the study period; with same quantity of cases for males and females. With ages between 2 and 17 years, and an average of 11.2 years. The four cases were from the inner states of Peru (Piura, Tumbes, Cajamarca and Junín). We present mandible resections as long as 15 cm for one side. All the cases underwent a surgical procedure with nasotracheal intubation; different mandible resections and a free fibula flap reconstruction, intermaxillary fixation and osteosynthesis with a mandible titanium plate and screws. We report an average blood loss of 467.5 cc, with a rank between 220 and 800 cc. Our transfusion average was 2.25 red blood cells pack by patient.